Sanfilippo's Textbook of Pediatric and Adolescent Gynecology - Sanfilippo, J. S. (Joseph S.); Lara-Torre, Eduardo; Gomez-Lobo, Veronica (Milton : CRC Press LLC, 2019)
This textbook provides a comprehensive review of all the common and less often encountered pediatric and adolescent gynecology problems in daily practice, both in the ambulatory as well as in the surgical setting. This new edition has been updated to keep it closely aligned to what general gynecologists or family physicians will want to know when dealing with a paediatric or adolescent patient, with accompanying videos.
22. Reproductive effects of obesity in adolescents23. Transgender care in adolescents; 24. Reproductive health care for adolescents with developmental delay; 25. Sexual abuse; 26. Fertility preservation in pediatric and adolescent girls; 27. Confidential care issues; 28. Family and cultural factors in pediatric gynecology; 29. Health-care transition; 30. Legal considerations in pediatric and adolescent obstetrics and gynecology; Appendix 1: Additional video resources; Appendix 2: Establishing a pediatric and adolescent gynecology clinical and educational program; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / General; MEDICAL / Family & General Practice; MEDICAL / Gynecology & Obstetrics; Pediatric gynecology; Adolescent gynecology